Febrile illness experience among Nigerian nomads - Akogun Oladele B; Gundiri Minnakur A; Badaki Jacqueline A; Njobdi Sani Y; Adesina Adedoyin O; Ogundahunsi Olumide T (BMC, 2012)
Abstract Background An understanding of the febrile illness experience of Nigerian nomadic Fulani is necessary for developing an appropriate strategy for extending malaria intervention services to them. An exploratory study of their malaria illness experience was carried out in Northern Nigeria preparatory to promoting malaria intervention among them. Methods Ethnographic tools including interviews, group discussions, informal conversations and living-in-camp observations were used for collecting information on local knowledge, perceived cause, severity and health seeking behaviour of nomadic Fulani in their dry season camps at the Gongola-Benue valley in Northeastern Nigeria. Results Nomadic Fulani regarded pabboje (a type of "fever" that is distinct from other fevers because it "comes today, goes tomorrow, returns the next") as their commonest health problem. Pabboje is associated with early rains, ripening corn and brightly coloured flora. Pabboje is inherent in all nomadic Fulani for which treatment is therefore unnecessary despite its interference with performance of duty such as herding. Traditional medicines are used to reduce the severity, and rituals carried out to make it permanently inactive or to divert its recurrence. Although modern antimalaria may make the severity of subsequent pabboje episodes worse, nomads seek treatment in private health facilities against fevers that are persistent using antimalarial medicines. The consent of the household head was essential for a sick child to be treated outside the camp. The most important issues in health service utilization among nomads are the belief that fever is a Fulani illness that needs no cure until a particular period, preference for private medicine vendors and the avoidance of health facilities. Conclusions Understanding nomadic Fulani beliefs about pabboje is useful for planning an acceptable community participatory fever management among them.